Efeito da imunização com enzimas recombinantes do metabolismo de nucleotídeos de Schistosoma mansoni sobre o desenvolvimento da esquistossomose mansônica experimental - Neris, Débora Meira (2012)
Schistosimiasis mansoni is a neglected chronic parasitic disease that affects thousands of people worldwide, caused by the trematode Schistosoma mansoni. In the infected host the disease is characterized by the presence of granuloma, imunnopathological response of the cellular infiltration against egg antigens. Thus, the host-parasite relation favors hepatosplenomegaly, acite and hepatic fibrosis. Current chemotherapy is based on the use of Praziquantel (PZQ), used against all species of Schistosoma spp for over 30 years. The main issue is that the PZQ is practically inactive against immature schistosomula and favors the resistance growth of the existent lineages, which makes the study for new drugs and vaccines that can contribute to the control of this disease even more urgent. One of the paths on the search for new therapeutic targets is the study of essential enzymes to the S. mansoni. In particular, it is known that the enzymes Adenylate Kinase 1 and 2 (ADK), Uridine cytidine Kinase 1 and 2 (UCK), Hypoxanthine guanine phosphoribosyltransferase (HGPRT) e Purine nucleoside phosphorilase 1 (PNP) are found on the metabolic pathways of the parasite s nucleotide, participating in the metabolism of purines and pyrimidines. Our goals in this study were to assess the immunization with these enzymes, using the S. mansoni cercariae infected murine model, and subsequently analyze the acting in oviposition and growth of adult worms. Our results showed that the immunization in Balb/c mice with the UCK enzyme was capable of inducing a specific immune response, which favored a significant reduction of the parasitic load (adult worms). However, it was not possible to observe significant reduction in the number of eliminated eggs. Regarding the immunization with PNP and HGPRT enzymes, the mice had a reduction in the number of eggs per gram of feces. The data obtained are considered interesting and can be new targets for immunotherapy against schistosomiasis mansoni. Thereby, new assays must be made with different dosages of the enzymes for a better assessment on how these enzymes modulate the parasitic load through the eggs reduction, reduction in the adult worms retrieving, as well as the antibody levels during the murine infection by the S.mansoni.